2011
DOI: 10.1063/1.3615952
|View full text |Cite
|
Sign up to set email alerts
|

Printed array of thin-dielectric metal-oxide-metal (MOM) tunneling diodes

Abstract: A large area array of metal-oxide-metal (MOM) tunneling diodes with an ultrathin dielectric ($3.6 nm aluminum oxide) have been fabricated via a transfer-printing process. The MOM diodes exhibit an excellent tunneling behavior that is suitable for rectifying high-frequency ac current into direct current (dc). Direct tunneling and Fowler-Nordheim tunneling have been observed over eight orders of magnitude in current density. The ratio between forward and reverse current is as large as two orders of magnitude. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…These thickness-dependent dielectric constants have been previously reported 28,29 and are believed to result from metal-dielectric interfacial effects, including a combination of field penetration into the metal, strain in the latticemismatched Al 2 O 3 layer and surface roughness. Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These thickness-dependent dielectric constants have been previously reported 28,29 and are believed to result from metal-dielectric interfacial effects, including a combination of field penetration into the metal, strain in the latticemismatched Al 2 O 3 layer and surface roughness. Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…3f, dotted line). To obtain agreement between the measured and calculated resonance frequencies, it was necessary to use a thickness-dependent dielectric constant for the Al 2 O 3 film 28,29 (see the Methods section and Supplementary Fig. S4 for details).…”
Section: Article Nature Communications | Doi: 101038/ncomms3361mentioning
confidence: 99%
“…[1][2][3][4][5][6][7]14,16,18,19 We recently showed that roughness at the bottom metalinsulator interface can dominate the I-V behavior of MIM diodes and that the use of atomically smooth bottom electrodes combined with high quality insulators deposited via atomic layer deposition (ALD) allowed for fabrication of high quality MIM diodes with well controlled quantum mechanical tunneling. 20,21 Therefore, we fabricate M 1 IIM 2 diodes using smooth amorphous metal ZrCuAlNi (ZCAN) bottom electrodes 22 and nanolaminate insulator bilayers of HfO 2 and Al 2 O 3 deposited via ALD.…”
mentioning
confidence: 99%
“…By combining bilayer tunnel barriers with the standard approach of asymmetric metal electrodes, we are able to achieve low voltage asymmetry and non-linearity exceeding both that of standard single layer asymmetric electrode metal-insulator-metal devices as well as symmetric electrode M 1 I 1 I 2 M 1 devices. Thin film metal-insulator-metal (MIM) tunnel devices have seen renewed interest for high speed applications [1][2][3] such as infrared (IR) detectors, 4-6 optical rectennas for IR energy harvesting, [7][8][9] and hot electron transistors, 10 as well as for macroelectronic applications such as backplanes for liquid-crystal displays (LCDs). 11,12 For many of these applications, highly asymmetric and non-linear current vs. voltage (I-V) behavior at low applied voltages is desired.…”
mentioning
confidence: 99%
“…Metal-oxide-metal (MOM) diodes have potential applications in the rectification of THz radiation because of their high switching speed of operation [1][2][3][4]. The use of dissimilar metals produces an asymmetric, non-linear I-V characteristic, resulting in a net current when rectifying.…”
Section: Introductionmentioning
confidence: 99%